Corrosion resistance of silicon-infiltrated silicon carbide (SiSiC). Issue 9 (15th June 2018) - Striegler, M.; Matthey, B.; Mühle, U.; Michaelis, A.; Herrmann, M.
Abstract: Silicon carbide ceramics have found widespread use due to their high corrosion stability. Both solid state-sintered silicon carbide, which has an extremely high corrosion resistance, and silicon-infiltrated silicon carbide are used for various applications. The latter material contains SiC as well as free silicon, which is less stable. Hence, in the present work, the corrosion behavior of silicon-infiltrated silicon carbide ceramics was investigated in NaOH solutions. Long-term corrosion experiments were conducted, and a method for analyzing the corrosion behavior in short-term experiments was developed. The short-term method is based on the accurate measurement of the corrosion depth by laser scanning microscopy on polished surfaces. The results of both methods were in good agreement. The advantage of the short-term method is that it provides information on changes in corrosion mechanisms and corrosion rates in the initial period and as a function of the impurities present. Preferential corrosion of Si at the interface to SiC was observed. TEM investigations revealed that this enhanced corrosion was caused by the segregation of impurities.